Should we declare war on the Turks?: Petrus Nannius' Declamatio de bello turcis inferendo (Leuven: Rutger Rescius, 1536) - Jaspers, Martijn (Spicilegium sacrum Lovaniense, 2024)
"This monograph delves into the content and impact of Petrus Nannius' Declamatio de bello Turcis inferendo, printed in 1536 by Rutger Rescius in Leuven. In a bid to gain recognition among the intelligentsia of Leuven and Brussels, Nannius advocated for European nations to initiate war against the Ottoman Empire. Serving as one of Nannius' first significant works, the success of the Declamatio established a crucial patronage relationship with Nicolaus Olahus and prompted multiple reprints. Following an introductory overview of the speech's historical context, this monograph scrutinizes Nannius' argumentation, emphasizing his strategic use of stereotypes to justify conflict with the Turks. It further explores the reception history of the Declamatio, encompassing its immediate reception in Leuven, subsequent reprints in German-speaking Europe, and a distinct 1611 edition tailored for the city of Alkmaar. Additionally, the thesis presents a Latin text edition based on the editio princeps as well as a first English translation accompanied by extensive annotations." --